2014
DOI: 10.1111/jam.12624
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and forecasting the distribution ofVibrio vulnificusin Chesapeake Bay

Abstract: This study uses one of the largest data sets compiled to model Vibrio in an estuary, enhances our understanding of environmental correlates with abundance, distribution and presence of potentially virulent strains and offers a method to forecast these pathogens that may be replicated in other regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 85 publications
11
69
1
1
Order By: Relevance
“…The species was first isolated from the liver and kidney of cultured rose snapper on the western coast of Mexico (Gomez-Gil et al, 2008) and was more recently isolated from oysters in North Carolina waters under conditions when detection of V. vulnificus on CPC + agar was rare (Froelich et al, 2012). The frequency of detection by qPCR (0.68 in water and 0.21 in oysters among all sites) is comparable to recent studies which have reported detection frequencies between 0.21 and 0.80 in water and an inability to detect V. vulnificus in unseeded oyster homogenates (Wetz et al, 2008;Jacobs et al, 2010;Franco et al, 2012;Froelich et al, 2012). The frequency of detection by qPCR (0.68 in water and 0.21 in oysters among all sites) is comparable to recent studies which have reported detection frequencies between 0.21 and 0.80 in water and an inability to detect V. vulnificus in unseeded oyster homogenates (Wetz et al, 2008;Jacobs et al, 2010;Franco et al, 2012;Froelich et al, 2012).…”
Section: Discussionsupporting
confidence: 72%
“…The species was first isolated from the liver and kidney of cultured rose snapper on the western coast of Mexico (Gomez-Gil et al, 2008) and was more recently isolated from oysters in North Carolina waters under conditions when detection of V. vulnificus on CPC + agar was rare (Froelich et al, 2012). The frequency of detection by qPCR (0.68 in water and 0.21 in oysters among all sites) is comparable to recent studies which have reported detection frequencies between 0.21 and 0.80 in water and an inability to detect V. vulnificus in unseeded oyster homogenates (Wetz et al, 2008;Jacobs et al, 2010;Franco et al, 2012;Froelich et al, 2012). The frequency of detection by qPCR (0.68 in water and 0.21 in oysters among all sites) is comparable to recent studies which have reported detection frequencies between 0.21 and 0.80 in water and an inability to detect V. vulnificus in unseeded oyster homogenates (Wetz et al, 2008;Jacobs et al, 2010;Franco et al, 2012;Froelich et al, 2012).…”
Section: Discussionsupporting
confidence: 72%
“…Examples include models for species of Vibrio (Constantin de Magny et al, 2010;Froelich et al, 2013;Jacobs et al, 2014), HABs (Milroy et al, 2008;Anderson, 2009;Moore et al, 2009;Brown et al, 2013), and indicator bacteria (Nevers and Whitman, 2011). In many cases, such models have been used in hydrodynamic modeling systems or used in conjunction with remotely sensed data to provide short term predictions, or early warning (Phillips et al, 2007;Brown et al, 2013;Grimes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The first is a previously published statistical model relating probability of occurrence of V. vulnificus to SST and SSS (Jacobs et al, 2014). For the purpose of this exercise, salinity was held constant at 12 psu, or approximately optimal salinity for V. vulnificus in Chesapeake Bay (Jacobs et al, 2010(Jacobs et al, , 2014.…”
Section: Seasonal Shiftsmentioning
confidence: 99%
See 2 more Smart Citations